2x+5=6x+1

Simple and best practice solution for 2x+5=6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+5=6x+1 equation:


Simplifying
2x + 5 = 6x + 1

Reorder the terms:
5 + 2x = 6x + 1

Reorder the terms:
5 + 2x = 1 + 6x

Solving
5 + 2x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 2x + -6x = 1 + 6x + -6x

Combine like terms: 2x + -6x = -4x
5 + -4x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -4x = 1 + 0
5 + -4x = 1

Add '-5' to each side of the equation.
5 + -5 + -4x = 1 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = 1 + -5
-4x = 1 + -5

Combine like terms: 1 + -5 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 2y+3=3 | | 2y+3=9 | | 10-5x=4x-44 | | 30-7h=10h-4 | | 3x+29=13x-71 | | 4p^2+24p=5 | | 5x+7=3+7x | | 6v=4(v+5) | | 3t+4=36 | | 7-90=2 | | 3x+3=6x-3 | | 2x*34-8=3 | | 4-2x=x+7 | | 2x-56=x | | 4m-2=2(2m-1) | | -3x-2=-38+6x | | 3t+4=4 | | 13+x=34 | | 7+2x=-5x-35 | | 7x-6y-9=0 | | 8=-5-2x | | 9-2x=-4x+5 | | 16=-8x | | lnx+ln(x+9)=2 | | 4(b-7)=7b+11 | | 5x-62=3x-8 | | 4(t-8)+20=20 | | 16=x-9 | | 107-3x=24x+20 | | 42x-28=30x+21 | | 4x-10=-1+3x | | 4x-10=-1 |

Equations solver categories